Implementation of ICARE Learning Model to Train Science Process Skills on Electrolyte and Non-Electrolyte Solution Materials for Educators at Muhammadiyah High School 10 GKB Gresik - Intan Wulandari; Muchlis Muchlis (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: Implementation of ICARE Learning Model to Train Science Process Skills on Electrolyte and Non-Electrolyte Solution Materials for Educators at Muhammadiyah High School 10 GKB Gresik. This research aims to describe the traceability of the ICARE learning model, student activities, student science process skills through the application of the ICARE learning model and student responses after the ICARE learning model is applied. The research used One Group Pretest-Postest Design with the subject of this study was X MIPA 1 students in Muhammadiyah 10 GKB Gresik, totaling 25 students. Data from the results of this study indicate that (1) The implementation of the ICARE learning model in electrolyte and non-electrolyte solution material during three meetings obtained an average percentage of 95,54%, 96,49%, and 97,78% with same good criteria. (2) The percentage of relevant student activity is greater than the activity of irrelevant students, at 93,02%, 95,15%, and 97,78%. (3) Student science process skills are increased where the average N-gain Score is 92% of students with high categories and 8% of students with moderate categories. In contrast, students' percentage of clastalentterity is 100%, with an average posttest value of 95,56. (4) The results of the students’ response application of the ICARE learning model received positive results with an average percentage of 90,4% on excellent criteriaKeywords: ICARE learning model, Student science process skills, electrolyte and non-electrolyte solution DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.05